Measuring the Burden on Family Caregivers of People With Cancer: Cross-cultural Translation and Psychometric Testing of the Caregiver Reaction Assessment–Indonesian Version. Issue 1 (January 2021) - Kristanti, Martina Sinta; Vernooij-Dassen, Myrra; Utarini, Adi; Effendy, Christantie; Engels, Yvonne
Abstract : Background: The Caregiver Reaction Assessment (CRA) is considered one of the well-developed instruments for measuring the multidimensional burden of family caregivers. To date, there is no available validated instrument to assist healthcare professionals in measuring the caregiver's burden in Indonesia. Objective: To translate the CRA from English into Indonesian and to conduct psychometric testing of this CRA–Indonesian version (CRA-ID) with family caregivers of patients with cancer. Methods: Cross-cultural translation and psychometric testing were conducted. Confirmatory factor analysis and exploratory factor analysis were performed to check, explore, and confirm the best model for the CRA-ID; internal consistency was also measured. Results: A total of 451 respondents participated, of whom 40 were involved in the feasibility testing. Confirmatory factor analysis with the original factors of the CRA revealed that the fit was not satisfactory, and adaptation was needed. Through exploratory factor analysis, the best model fit was developed, and confirmatory factor analysis was performed again. Five factors from the original instrument were confirmed with an explained variance of 54.89%. Almost all items in the CRA-ID appeared to have a similar structure as the original version. Cronbach's α 's ranged between .64 and .81. Conclusions: The CRA-ID appeared to be feasible, valid, and reliable for measuring the burden of family caregivers of patients with cancer in Indonesia. Implications for Practice: Nurses can use the CRA-ID to measure family caregivers' burden. Its availability in the Indonesian language enhances the opportunity to conduct international comparisons of family caregiver burden using the same instrument. Abstract : Supplemental digital content is available in the text.